Perancangan Redesain Kemasan Produk Olahan Camilan Pawon Ara Untuk Meningkatkan Brand Value - Kristian Mahardika Suryanto; Bayu Setiawan; Widyasari Widyasari (CV. ULIL ALBAB CORP, 2024)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia produce many types of products, especially snacks in the form of chips. One of the problems often faced by MSMEs is the use of simple packaging, so that the product looks less attractive and has difficulty competing with manufactured products. This study aims to increase the brand value of MSME Pawon Ara through redesigning the packaging of several snack products. This packaging redesign is expected to meet market standards, attract consumers' attention, and increase purchasing interest. The methods used in this study are qualitative and quantitative approaches. Qualitative data collection was carried out through field observations, in-depth interviews with the owner of Pawon Ara, and interviews with branding experts. Meanwhile, quantitative data was obtained by distributing questionnaires to the people of Sidoarjo and its surroundings via social media Instagram and WhatsApp. The results of the study showed that attractive packaging design can increase consumer purchasing interest, so that products are more competitive in the modern market and have the potential to increase sales